Efek Pemberian Decanter Solid terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq) dengan Media Tanah Bekas Lahan Tambang Batu Bara di Pembibitan Utama - Anis Tatik Maryani (Universitas Sebelas Maret, 2018)
Land resource hoarding coal post is supporting agricultural development. Experiment on the use of the media to land former coal mines that are expected to become soil ameliorant media or media after seedlings seeds moved into the field. The purpose of this study is 1) Determining the growth of oil palm seedlings with soil medium former coal mining areas. 2) Determining the decanter solid dose of the best on the growth of oil palm seedlings on former pasture land of coal mines in the main nursery. Design of experiment was randomized block design (RBD) with 7 dose treatment levels of decanter solid, there is no decanter solid, 100, 200, 300, 400, 500, and 600 g/polybag. Each treatment was replicated four times, so there are 28 experimental units. Each experimental unit consisted of three plants and as an each of them as plant sample, thus totally there are 84 plants. Observed variables include the increase of plant height, plant diameter (cm) and leaf area (cm2) as well as the rate of plant growth and Seed Quality Index. Results of the research show that in general the administration of decanter solid on the growth of seedlings of oil palm with former land area coal mines provide better growth on the plant height, diameter, number of leaves, leaf area, increase the rate of plant growth as well as seed quality index compared to oil palm seedlings without any decanter solid. Decanter solid 400 g/polybag is the best for the growth of oil palm seedlings.